2018
DOI: 10.1093/jisesa/iey022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Life Table Parameters and Digestive Physiology of Rhyzopertha dominica (Coleoptera: Bostrichidae) Fed on Various Barley Cultivars

Abstract: In this study, the effect of 20 barley cultivars were evaluated on the life table parameters and digestive enzymatic activity of the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) under laboratory conditions (28 ± 1°C, 60 ± 5% RH, and a photoperiod of 16:8 (L:D) h). Among barley cultivars tested developmental time of R. dominica immature stages was longest on cultivar Bahman (61.00) and shortest on Mahoor (46.60 d). The lowest realized fecundities were recorded for insects reared on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Different cultivars of a host plant play a crucial role in population growth and food utilization of insects (Golizadeh and Razmjou, 2010; Alami et al ., 2014; Nemati-Kalkhoran et al ., 2018; Mobarak et al ., 2020). Till date, no reports are available on D. indica using age-stage, two-sex life table, and further, the biology of D. indica on T. anguina is reported for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different cultivars of a host plant play a crucial role in population growth and food utilization of insects (Golizadeh and Razmjou, 2010; Alami et al ., 2014; Nemati-Kalkhoran et al ., 2018; Mobarak et al ., 2020). Till date, no reports are available on D. indica using age-stage, two-sex life table, and further, the biology of D. indica on T. anguina is reported for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic rate of increase ( r m ) and finite rate of increase ( λ ) can exactly predict the overall population growth, development and fecundity of an insect population, and are considered as important parameters in measuring population growth potential (Karimi-Pormehr et al ., 2018; Nemati-Kalkhoran et al ., 2018; Das et al ., 2019; Mobarak et al ., 2020). The r m was the lowest on Polo No.…”
Section: Discussionmentioning
confidence: 99%
“…Crop cultivars impact insect life table parameters and activities of detoxifying enzyme (Li et al, 2009;Golizadeh & Abedi, 2017;Güncan & Gümüş, 2017;Zheng et al, 2017;Nemati-Kalkhoran et al, 2018) and whereas SBPH may successfully survive on a range of rice and wheat cultivars, the level of adaptability to them may vary (Li et al, 2009;Zheng et al, 2017). For example, Liu et al (2011) found out that SBPH survival rates and the activities of detoxification enzymes varied among individuals reared on four cultivars of rice.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure insects to a sublethal amount of insecticides, which result from either insecticides misapplication or degradation can generate physiological, behavioral, and survival responses (Biondi et al, 2012;Desneux et al, 2007). Several factors affect Life table parameters of khapra beetle include crop cultivars (Majd- Marani et al, 2017;Nemati-Kalkhoran et al, 2018), pressure (Finkelman et al, 2006), irradiation (Sedaghat et al, 2014;Ubaid, 2016), exposure to chemicals (Ali et al, 2018;Shakoori et al, 2016). Sublethal concentrations of tricalcium phosphate prolonged generation time (T), and increased gross reproductive rate (GRR) of T. granaries, (Kraszpulski et al, 1987).…”
Section: Discussionmentioning
confidence: 99%